STUDI PERBANDINGAN EKONOMI REGIONAL KALIMANTAN TIMUR DAN RIAU - Mubyarto Mubyarto (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 1991)
A financially constrained central goverment no longer has the capacity to fund major development projects throughout the country. Jakarta must look more to the regions for ideas,money and initiatives.Reforms are required in regional authority, and innational programmes-from rice to foods policies and transmigration-which have a regional impact. The